Genetic analysis of selected quantitative attributes in maize genotypes exploiting 6 × 6 diallel mapping population - Maliha, Mushfika Tasneem; Hossain, Akbar; Rahman, Mobinur; Islam, Sazia; Alam, Md Shafiqul; Khanam, Rokeya; Raihan, Mohammad Sharif (Annals of Bangladesh Agriculture, 2025)
Combining ability and heterosis for nine quantitative characters of six parental genotypes and 15 F1s derived from a 6×6 diallel cross without reciprocal was assessed. Ranking of the parents for seventeen characters on general combining ability indicated that the parental genotype P3 was the best general combiner for plant height, number of kernels per cob, test weight and the genotype P6 for hundred kernel weight. The estimates of specific combining ability (SCA) effect revealed that in most of the cases, combinations of high × low or even low × low exhibited high SCA effect for many characters rather than high × high cross combinations indicating the importance of gene interaction. Based on SCA performances the hybrids H4 (P1×P5) and H13(P4×P5) were the best specific combiners for test weight. Test weight is the weight of a specific volume of grain. The hybrids H11, H5 and H15 were the best specific combiners for plant height, cob breath and number of kernels per row respectively. Heterosis was the highest in H4 (P1×P5) for mainly hundred kernel weight followed by H6 (P2×P3) over mid parent. The genetic analysis of maize genotypes using a 6 × 6 diallel cross revealed significant variation and combining abilities for key quantitative traits, offering a strong foundation for future hybrid breeding programs. Ann. Bangladesh Agric. 28(2): 137-153